(untitled) (Revista científica Olimpia, 2019)
This study was carried up in the “Grandparents Circle Vilma Espín” in Bayamo City. The sample was formed by 31 elderly (29 women y 2 men), with chronological aged average of 67, 4 years old. The general objective is to design a psychosocial actions system from Grandparents Circle, for to raise the subjective well-being in these older persons. With investigation methods of theoretic and empiric knowledge, the author obtained a psychosocial characterization, the creation and application of the actions system. The result was satisfactory in the raise of the subjective well-being. These results constitute a practical contribution to process of the communitarian physical activity for elderly.